Uncoercible Communication - Tuinstra, Dwight; Benaloh, Josh (Microsoft, 1994)
This paper describes a model and method whereby one agent can send a private message to another over a public channel from within a " environment in which the sending agent may be subject to extreme coercion both before and after the sending of the message. Coercive forces may demand that certain information be or not be sent, may monitor the channel over which the transmission will take place, and may require that the sending agent reveal all information after the transmission is complete. Nevertheless, the sending agent may claim to have sent one message while actually having sent another and will be unable to provide any kind of receipt to the coercer to show what message was actually sent.